2008
DOI: 10.1016/j.physletb.2008.07.081
|View full text |Cite
|
Sign up to set email alerts
|

Low-lying proton intruder state in 13B

Abstract: The neturon rich nucleus 13 B was studied via the proton transfer reaction 4 He( 12 Be, 13 Bγ) at 50A MeV. The known 4.83-MeV excited state was strongly populated and its spin and parity were assigned to 1/2 + by comparing the angular differential cross section data with DWBA calculations. This low-lying 1/2 + state is interpreted as a proton intruder state and indicates a deformation of the nucleus.The existence of intruder states in light neutron-rich unstable nuclei is often considered to be evidence for on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
4
13
0
Order By: Relevance
“…Assuming J π = 1/2 + , the deduced spectroscopic factor is C 2 S = 0.13±0.02, or about 5% of that of the ground state. A J π = 1/2 + assignment agrees with the results of Ota et al, where the 4.83 MeV state was populated with a proton-stripping spectroscopic strength of C 2 S = 0.2 ± 0.02 [15]. These observations imply that π(1s) 2 (0p) −2 admixtures are present in the 14 C ground-state wave function.…”
Section: B Distorted-wave Born Approximation Calculations and Spectrsupporting
confidence: 90%
See 1 more Smart Citation
“…Assuming J π = 1/2 + , the deduced spectroscopic factor is C 2 S = 0.13±0.02, or about 5% of that of the ground state. A J π = 1/2 + assignment agrees with the results of Ota et al, where the 4.83 MeV state was populated with a proton-stripping spectroscopic strength of C 2 S = 0.2 ± 0.02 [15]. These observations imply that π(1s) 2 (0p) −2 admixtures are present in the 14 C ground-state wave function.…”
Section: B Distorted-wave Born Approximation Calculations and Spectrsupporting
confidence: 90%
“…A recent lifetime measurement has suggested that the lowest negative-parity excited state at 3.53 MeV had J π =3/2 − and possessed neutron 2p − 2h character [14]. Finally, a J π = 1/2 + proton-"intruder" state was reported in 13 B from the 14 Be(α, t) 13 B reaction [15] at 4.83 MeV excitation energy. Population of this state in the 14 C(d, 3 He) 13 B reaction may suggest some admixtures of proton-(sd)…”
Section: Introductionmentioning
confidence: 96%
“…1 is another evidence of the selectivity of the ( 18 O, 16 O) reaction. Indeed, states excited in the one nucleon transfer reactions are scarcely populated, as for example the 4.8 MeV state which has been recently identified as a proton intruder state [2]. Finally, a qualitative comparison with the 14 C excitation energy spectrum populated via the ( 18 O, 16 O) at 85 MeV is reported in Fig.…”
Section: Preliminary Resultsmentioning
confidence: 95%
“…The N = 8 nucleus 13 B is, therefore, expected to be on the borderline between these two opposite regimes. Recent results have demonstrated such peculiarity, showing that the 13 B isotope exhibits both low lying proton and neutron intruder states indicating a reduced shell gap between p and sd shells [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Rauscher et al [10] estimated the uncertainties of the reaction rates for the 11 B(n,γ) and 12 B(n,γ) reactions to be a factor of 2, based on the limited spectroscopic information on 12 B and 13 B and considering both direct and resonant captures. Although there have been several investigations of the poorly known structure of 13 B [11], such as single-nucleon knockout [12], a proton intruder study [13], and a search for isobaric analog states [14], as well as theoretical efforts in cluster studies [15], the spin-parities of most excited states are not well determined [16].…”
Section: Introductionmentioning
confidence: 99%